PEMBELAJARAN SPEAKING MELALUI PENDEKATAN CONTENT-BASED INSTRUCTION BAGI GURU-GURU SMA/SMK HARAPAN BATAM - Ambalegin Ambalegin; Melly Siska Suryani (PUAN INDONESIA, 2019)
The aim of national education in Law No.20 of 2003 is to develop the potential of responsible, healthy, knowledgeable, capable, creative, independent, democratic, and noble students who believe God Almighty. The noble aim of education in Indonesia is to implement attitudes, knowledge, and skills. Implementation of curriculum 2013 has a positive impact in improving the quality of education in Indonesia. In each implementation of teaching, students are taught to prioritize inductive thought more than deductive thought because curriculum 2013 uses a scientific approach. Learning English is the compalsory subject that uses a scientific approach in high schools. English teachers must have competence in transferring knowledge. But they are constrained in application of a scientific text-based approach to teaching English. The purpose of this training is to apply the Content-Based Instruction (CBI) approach to English language learning, especially for teaching speaking at high schools. The method is in the form of interviews (pretest), discussion, and direct practice (posttest) by using Content-Based Instruction approach based on scientific texts. The results of the training are expected to be able to produce teachers who are competent in teaching English and creating the enjoyable learning English so that learners can develop the potential of students.